1997
DOI: 10.1136/jcp.50.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical expression of tissue specific transcription factor-1 in lung carcinoma.

Abstract: Aims-To investigate the immunocytochemical expression of the tissue specific transcription factor-1 (TTF-1) on cytological specimens of small cell lung carcinoma (SCLC) and to establish its value in the cytological diagnosis of lung cancer. Methods-For each case, the diagnosis was made on cytological specimens and confirmed on subsequent bronchial biopsy specimens. TTF-l was detected immunocytochemically using the avidinbiotin complex technique with a rabbit antiserum. Expression of TTF-1 was evaluated in 41 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
86
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(94 citation statements)
references
References 7 publications
5
86
1
Order By: Relevance
“…Interestingly, PAX9, TTF-1, and NKX2-8 activation status correlates with the tissue subtype of non-small-cell lung cancer; the majority of the adenocarcinoma samples exhibit a high probability of PAX9 and TTF-1 activation (Fig. 2B) relative to the squamous cell carcinoma samples, in line with published reports that TTF-1 protein expression is higher in adenocarcinoma than in squamous cell carcinoma (18)(19)(20)(21). In contrast to TTF-1 and PAX9, NKX2-8 deregulation is more prominent in squamous cell carcinomas.…”
Section: Ttf-1 Nkx2-8 and Pax9 Activation Correlates With Molecularsupporting
confidence: 77%
“…Interestingly, PAX9, TTF-1, and NKX2-8 activation status correlates with the tissue subtype of non-small-cell lung cancer; the majority of the adenocarcinoma samples exhibit a high probability of PAX9 and TTF-1 activation (Fig. 2B) relative to the squamous cell carcinoma samples, in line with published reports that TTF-1 protein expression is higher in adenocarcinoma than in squamous cell carcinoma (18)(19)(20)(21). In contrast to TTF-1 and PAX9, NKX2-8 deregulation is more prominent in squamous cell carcinomas.…”
Section: Ttf-1 Nkx2-8 and Pax9 Activation Correlates With Molecularsupporting
confidence: 77%
“…The 14q13.3 amplicon does not appear to be limited to a specific subtype of lung cancer. This is particularly intriguing in that Ttf1 protein is rarely detected in the SCC type of lung cancer based on multiple studies in the literature (21)(22)(23)(24). Consistent with the literature, in multiple squamous lung cancer cell lines (including the amplified H2170 cells), we have not been able to detect the protein expression of TTF1 by using a highly specific monoclonal antibody [clone 8G7G3/1 (25)] (Fig.…”
Section: The 14q133 Amplicon Contains Three Transcription Factor Genessupporting
confidence: 60%
“…In some of the earlier studies, which used a polyclonal antibody against TTF-1, positivity for this protein was reported in 11-23% of the squamous carcinomas of the lung. [68][69][70] Subsequent investigations using the 8G7G3/1 monoclonal antibody, however, have shown that TTF-1 expression is usually absent in these tumors. 47,[71][72][73][74][75] In the present investigation, none of the squamous carcinomas of the lung or the mesotheliomas exhibited TTF-1 positivity.…”
Section: Discussionmentioning
confidence: 99%